Promoting students' health awareness and higher order thinking skills using E-projects strategy in learning physical and health education - Taghread Ahmed Elsayed Ahmed; Heba Ali Ibrahim Seleem; Ghada Mohamed Youssef Elsayed; Nour Taha Ebrahem Housen; Mona Abdelmoneim; Nagla Eltanahi; Naglaa Mohamed Roby Sofy; Sara Nashat Housny Elshltawy (Wolters Kluwer Medknow Publications, 2023)
BACKGROUND: Health awareness and higher-order thinking skills have become important requirements for higher education students because these skills make students effective problem-solvers. So, this study aimed to promote students' health awareness and higher-order thinking skills through the E-projects strategy in learning physical and health education.MATERIALS AND METHODS: The experimental study was conducted at Imam Abdulrahman bin Faisal University, KSA, from September 5 to December 23, 2021. The study was conducted on 250 students (age: 18.23 ± 0.66 years). They were divided into 10 groups each group prepared a different E-project according to the intended learning outcomes of the physical and health education course. To collect data, two scales were designed, the first to measure health awareness and the second to measure higher-order thinking skills. Moreover, the ADDIE model was used during the implementation of the E-projects strategy in learning. The collected data were analyzed using SPSS version 22 software. The level of significance was set at P ≤ 0.05.RESULTS: The results showed that there were statistically significant differences between pre and post-measurement in all studied variables in favor of post-tests for the experimental group, as the mean differences in health awareness were (29.33) and ranged from (8.63: 10.01) in higher-order thinking skills (HOTS), the percentages of improvement for health awareness was 14.66%. While the rates of improvement in the higher-order thinking skills ranged between 26.28% to 48.78%.CONCLUSION: The major conclusion drawn from this study was that the application of the E-projects strategy in learning physical and health education using the ADDIE model significantly influences the improvement of students' health awareness and higher-order thinking skills in higher education.